Alive - Sigler, Scott (New York : Del Rey, an imprint of Random House, 2015)
Waking up in a mysterious enclosed space with no memory of their identities, a group of adults uncovers evidence of a long-past war and the horrifying realities of their confinement.
Keywords: Captivity -- Fiction; Survival -- Fiction; Amnesia -- Fiction; Science fiction; Suspense fiction